2018
DOI: 10.1111/conl.12454
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing biodiversity conservation and carbon stocking in restored tropical forests

Abstract: Assessing the conservation value of restoration plantings is critical to support the global forest landscape restoration movement. We assessed the implications of tree species selection in the restoration of Brazil's Atlantic Forest regarding carbon stocking and species conservation. This assessment was based on a comprehensive dataset of seedling acquisition records from 961 restoration projects,  more than14 million seedlings, 192 forest remnants, and functional data from 1,223 tree species. We found that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 45 publications
3
54
0
6
Order By: Relevance
“…Glassman, and Genipa americana L.). This highlights the value of restoration plantations for the conservation of largeseeded tropical trees that usually have reduced dispersal across degraded landscapes , Brancalion et al 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glassman, and Genipa americana L.). This highlights the value of restoration plantations for the conservation of largeseeded tropical trees that usually have reduced dispersal across degraded landscapes , Brancalion et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Forest-based climate mitigation emerged as a key component of the recent Paris Climate Agreement (Grassi et al 2017), which confirmed the ongoing political momentum for promoting reforestation and forest restoration. While tropical deforestation has substantially contributed to the increase of atmospheric CO 2 in recent decades (Zarin 2012), the accumulation of biomass in reforested or restored tropical areas is widely considered as a major tool for future climate change mitigation (Alexander et al 2011, Hulvey et al 2013, Locatelli et al 2015, Chazdon et al 2016, Brancalion et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…; Brancalion et al . ). Our results confirm others that found a fast recovery of secondary forests in terms of species diversity but a very slow recovery rate in terms of species composition (van Breugel et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, the overall variety and quantities of animal-dispersed species are below those expected for tropical forests, which varies from 70 to 94% of woody species (Almeida-Neto et al 2008; Bello et al 2017). As shown by Brancalion et al (2018), large-seeded animal-dispersed species are particularly underrepresented in restoration projects, with consequences for carbon storage and restoration outcomes. We recommend enhancement on the proportion of animal-dispersed species in plant nurseries, since plants consumed and dispersed by animals are notably important in degraded landscapes, where maintenance of plant-animal interactions are essential to enable restoration of ecological processes, biological fluxes and ecosystem services (Howe 2016; Brancalion et al 2018).…”
Section: Discussionmentioning
confidence: 99%